Environmentally Friendly Antifouling Metabolites from Red Sea Organisms - Sultan Semran Al-Lihaibi; Ahmed Abdel-Lateff; Walied Mohamed Alarif; Hajer Saeed Alorfi; Yasuyuki Nogata; Tatsufumi Okino (Journal of Chemistry, 2019)
Seventy-one marine organisms representing different classes of marine fauna and flora were collected from the Red Sea. They include sponges, hydrozoan, soft corals, sea cucumber, ascidian, cyanobacteria, and macroalgae. The methanolic extracts were evaluated for their toxicity and settlement inhibition effects by using cultured Balanus amphitrite. Thirty-three extracts displayed antifouling effects: four samples were highly potent at 1 μg/mL with a percentage of settlement inhibition above 31%, twenty-two were potent at 10 μg/mL with a percentage of settlement inhibition between 16 and 30%, and seven were active at 10 μg/mL with a percentage of settlement inhibition between 0 and 15%. Two promising extracts were purified by employing several chromatographic techniques, leading to the isolation of 12 known compounds. The isolated compounds were evaluated for their antifouling activities and demonstrated potent antifouling effects with EC50 values of less than 10 μg/mL.